An Overview of Recent Progress in the Study of Distributed Multi-Agent Coordination - Cao, Yongcan; Yu, Wenwu; Ren, Wei; Chen, Guanrong (IEEE transactions on industrial informatics, 2013)
This paper reviews some main results and progress in distributed multi-agent coordination, focusing on papers published in major control systems and robotics journals since 2006. Distributed coordination of multiple vehicles, including unmanned aerial vehicles, unmanned ground vehicles, and unmanned underwater vehicles, has been a very active research subject studied extensively by the systems and control community. The recent results in this area are categorized into several directions, such as consensus, formation control, optimization, and estimation. After the review, a short discussion section is included to summarize the existing research and to propose several promising research directions along with some open problems that are deemed important for further investigations.